Chrysanthemum - Henkes, Kevin (New York : Greenwillow Books, 1991)
Chrysanthemum loves her name, until she starts going to school and the other children make fun of it.
Wilson's Children
Elem. School Library Collection
School Library Journal
4.2
K-3
Keywords: Names, Personal -- Fiction; Schools -- Fiction; Personal names -- Fiction; School stories